Reduced Serotonin Transporter Availability Decreases Prefrontal Control of the Amygdala - Volman, Inge (J Neurosci, 2013)
After a threatening event, the risk of developing social psychopathologies is increased in short-allele (s) carriers of the serotonin transporter gene. The amygdala becomes overresponsive to emotional stimuli, an effect that could be driven by local hypersensitivity or by reduced prefrontal regulation. This study distinguishes between these two hypotheses by using dynamic causal modeling of fMRI data acquired in a preselected cohort of human s-carriers and homozygous long-allele carriers. Increased amygdala activity in s-carriers originates from reduced prefrontal inhibitory regulation when social emotional behavior needs to be controlled, suggesting a mechanism for increased vulnerability to psychopathologies.